2022
DOI: 10.3390/ijms23063410
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Probes Based on Rare-Earth Doped Strontium Aluminates with Long-Lasting Phosphorescent Properties for In Vitro Optical IMAGING

Abstract: In recent decades, the demand for biomedical imaging tools has grown very rapidly as a key feature for biomedical research and diagnostic applications. Particularly, fluorescence imaging has gained increased attention as a non-invasive, inexpensive technique that allows real-time imaging. However, tissue auto-fluorescence under external illumination, together with a weak tissue penetration of low wavelength excitation light, largely restricts the application of the technique. Accordingly, new types of fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This protocol aims to elucidate the luminescent properties of the nanocomposite in vitro and their organelle colocalization, internalization, and biological stability in living cells. This will allow the development of a new generation of hybrid organic–inorganic biomarkers for cancer detection and monitoring. , …”
Section: Challenges For the In Vitro Delivery And Molecular Imaging W...mentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol aims to elucidate the luminescent properties of the nanocomposite in vitro and their organelle colocalization, internalization, and biological stability in living cells. This will allow the development of a new generation of hybrid organic–inorganic biomarkers for cancer detection and monitoring. , …”
Section: Challenges For the In Vitro Delivery And Molecular Imaging W...mentioning
confidence: 99%
“…Mesoporous silica nanoparticles (MSNs) are gaining increasing interest as the shell component of hybrid nanoparticles (e.g., as a crucial component of the core–shell entities with magnetic cores, or encapsulating inorganic oxides cores for biomedical applications): this important component of core–shell materials explored as nanomedicine components for drug delivery and specific labeling with fluorophores or radioisotopes. This ceramic layer acts as a biocompatible component in multifunctional nanomedicines to their several attractive features such as good biocompatibility, large surface area, tunable pore sizes, controllable particles sizes and shapes, and dual-functional surfaces (exterior and interior). , The light transparency of the silica matrix enables the excitation and emission light to pass through the silica framework, as necessary for bioimaging applications. The chemical functionalization of such shells with targeting groups relies on the ability to incorporate bio-orthogonal linkers having the ability to attach “addresses” which in turn will tackle clinical needs for synthetic scaffolds appropriate as drug delivery systems for the biological imaging space.…”
Section: Challenges For the In Vitro Delivery And Molecular Imaging W...mentioning
confidence: 99%
“…9 Subsequently, several studies reported a development in PLN for biosensing and in vivo imaging. 10,11 However, the theragnostic ability of PLN has not been well explored. In one such study, nanoparticles were synthesized with NIR persistent luminescence for imaging and were co-encapsulated with doxorubicin and a photosensitizer (Si-Pc) for chemo-/photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…22 In the past few decades, the time-gated luminescence (TGL) detection technique using lanthanide complexes as labels or probes has been widely used to achieve highly sensitive luminescence bioassays. 23 The long-lived luminescence of these complexes enables them to be used for detecting target analytes in complicated samples with high signal-to-noise ratios since short-lived autofluorescence from biological specimens can be efficiently eliminated. 24 Thus the bimodal probes for TGL imaging (TGLI)-MRI using luminescent lanthanide complexes as luminophores have attracted great attention.…”
Section: Introductionmentioning
confidence: 99%